2018
DOI: 10.1007/s00439-018-1887-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder

Abstract: Many genetic causes of developmental delay and/or intellectual disability (DD/ID) are extremely rare, and robust discovery of these requires both large-scale DNA sequencing and data sharing. Here we describe a GeneMatcher collaboration which led to a cohort of 13 affected individuals harboring protein-altering variants, 11 of which are de novo, in MED13; the only inherited variant was transmitted to an affected child from an affected mother. All patients had intellectual disability and/or developmental delays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 48 publications
4
51
0
Order By: Relevance
“…For many of the genes listed in Table S1 (see families M9300163, M9300035, M9300014, M8800189 and M8900019), mutations in patients with ID have only been reported very recently, including VPS13C ; BOD1, TTI1, NEURL4 ; ATP13A1, a paralog of ATP13A2 , which is associated with autosomal recessive early‐onset parkinsonism, ceroid lipofuscinosis and ID, as well as MED13 . Thus, our study confirms their identity as ID genes.…”
Section: Resultsmentioning
confidence: 99%
“…For many of the genes listed in Table S1 (see families M9300163, M9300035, M9300014, M8800189 and M8900019), mutations in patients with ID have only been reported very recently, including VPS13C ; BOD1, TTI1, NEURL4 ; ATP13A1, a paralog of ATP13A2 , which is associated with autosomal recessive early‐onset parkinsonism, ceroid lipofuscinosis and ID, as well as MED13 . Thus, our study confirms their identity as ID genes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, another interpretation of the knockout results is that removing Med13 or Med13L may invoke a gene dosage-related phenotype. For example, recent studies found that MED13 or MED13L haploinsufficiency results in several overlapping, but not identical, developmental syndromes (41)(42)(43)(44)(45)(46). Therefore, transcriptional control by Med13 and Med13L may be exquisitely sensitive to gene copy number.…”
Section: Discussionmentioning
confidence: 99%
“…• Similarly, subjects with haplo-insufficiently of MED13L show ID and severe speech delay; congenital heart defects are found in 20-50% of patients 79,81 . In preclinical studies, haploinsufficiency of MED13L shows defects in both neuronal migration and differentiation 82,83 . • ADNP variants are reported in children with autism and ID who carry a diagnosis of Helsmoortel-Van der Aa syndrome 84 .…”
Section: Genementioning
confidence: 99%